Cover Feature: Linker‐Modulated Peroxide Electrosynthesis Using Metal‐Organic Nanosheets (ChemElectroChem 10/2022). Issue 10 (11th April 2022) - Kuruvinashetti, Kiran; Kornienko, Nikolay
Abstract : The Cover Feature illustrates metal‐organic nanosheet catalysts, whose activity for oxygen reduction to peroxide can be rationally tuned via appending functional groups onto their linkers. More information can be found in the Research Article by K. Kuruvinashetti and N. Kornienko .